Sintesis Gaya Belajar dan Media Pembelajaran untuk Mengoptimalkan Keterampilan Abad ke-21 dalam Pendidikan Vokasi - Ega Devianti; Robinson Situmorang; Mita Septiani (Prosiding Seminar Nasional Ilmu Pendidikan, 2025)
This study aims to synthesize the relationship between learning styles and instructional media in optimizing 21st-century skills among Diploma Three (D3) vocational students. The research employed a simple literature review method by analyzing 20 national and international journal articles published between 2018 and 2024. The results reveal that the alignment between learning styles (visual, auditory, kinesthetic) and the types of instructional media significantly influences the development of critical thinking, creativity, communication, and collaboration skills. Technology-based media, such as interactive videos, learning management systems (LMS), and virtual simulations, effectively accommodate diverse learning preferences while enhancing students’ motivation and engagement. Furthermore, integrating such media not only supports individual learning needs but also fosters a more dynamic and inclusive educational environment. The study concludes that integrating learning styles with digital-based media serves as an effective strategy to produce competent and adaptive vocational graduates who are well-prepared to face the challenges of Industry 4.0 and Society 5.0.